1999
DOI: 10.3923/pjbs.1999.1634.1636
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Strongylosis in Equines with Special Emphasis on Hematology and Chemotherapy

Abstract: The prevalence of strongylosis was found to 31.7 percent being 34.0, 30.0 and 31.0 percent, in stud, tonga and riding horses, respectively. Blood picture of the naturally infected animals showed normocytic and normochromic anaemia. Invermectin at the dose level of 0.4 mg kgG 1 completely eliminated the egg burden from day 14 post treatment onward. Similar trend is followed at 0.2 mg kgG 1 dose level with a small variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
6
0
0
Order By: Relevance
“…The low temperature, high percentage of relative humidity and heavy rain fall cause decrease in presence percentage as these conditions do not suite the development / survival of strongyle eggs / larvae. This was also in accordance with Hutchinson et al (1989) and Sipra et al (1999).…”
Section: Discussionsupporting
confidence: 90%
“…The low temperature, high percentage of relative humidity and heavy rain fall cause decrease in presence percentage as these conditions do not suite the development / survival of strongyle eggs / larvae. This was also in accordance with Hutchinson et al (1989) and Sipra et al (1999).…”
Section: Discussionsupporting
confidence: 90%
“…In the current finding the prevalence of strongyle was 35.4% which is consistent with the study of Spira et al [29] in Pakistan, Seri et al [30] in Khartoum Sudan; and Worku and Afera [28] with the report of 31.7%, 35.8% and 32.6% respectively. However the previous studies in Ethiopia by Ayele et al [13], Gizachew et al [17], Mulate [31], and Yoseph et al [15] reported the prevalence of Strongyle higher than 99% which was by far higher than the current study.…”
Section: Discussionsupporting
confidence: 82%
“…The mean value of monocytes (%) was significantly decreased (p< 0.05) from 3.663±0.10 to 2.892±0.06 % in non-infected and infected horses, respectively. These findings were in accordance with several workers including Sipra et al, (1999); Kachhawa (2013); Mudgal (2013); Waqas et al, (2014) and Salem et al, (2015). Monocytes are capable of phagocytizing and digesting the particulate matter, such as cellular debris.…”
Section: Introductionsupporting
confidence: 92%
“…The mean value of lymphocytes (%) was significantly decreased (p< 0.05) from 42.267±0.66 to 39.856±0.26 % in noninfected and infected horses, respectively. These results are in conformity with the findings of Sipra et al, (1999); Kumar (2012); Kachhawa (2013); Mudgal (2013); Khan et al, (2014) and Salem et al, (2015).Decreased percentage of lymphocytes were suggestive of active participation of lymphocytes in immune mechanism to evade the helminth antigen. Hence their numbers gradually decreased.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation